Mucosal immune tolerance at the ocular surface in health and disease - Galletti, Jeremías Gastón (2017)
The ocular surface is constantly exposed to environmental irritants, allergens and pathogens, against which it can mount a prompt immune response to preserve its integrity. But to avoid unnecessary inflammation, the ocular surface’s mucosal immune system must also discriminate between harmless and potentially dangerous antigens, a seemingly complicated task. Despite its unique features, the ocular surface is a mucosal lining, and as such, it shares some homeostatic and pathophysiological mechanisms with other mucosal surfaces. The purpose of this review is to explore the mucosal homeostatic immune function of the ocular surface in both the healthy and diseased states, with a special focus on mucosal immunology concepts. The information discussed in this review has been retrieved by PubMed searches for literature published from January 1981 to October 2016.